2003
DOI: 10.1002/pmic.200300541
|View full text |Cite
|
Sign up to set email alerts
|

ProteoChip: A highly sensitive protein microarray prepared by a novel method of protein immobilization for application of protein‐protein interaction studies

Abstract: We have developed a highly sensitive microarray protein chip, ProteoChip, coated with ProLinker, novel calixcrown derivatives with a bifunctional coupling property that permits efficient immobilization of capture proteins on solid matrixes and makes high-throughput analysis of protein-protein interactions possible. The analysis of quartz crystal microbalance showed that both monoclonal antibody (mAb) and antigen (Ag) bound to the gold film of the sensor surface coated with ProLinker B and that it is useful for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(140 citation statements)
references
References 33 publications
4
135
0
1
Order By: Relevance
“…In order to determine low concentrations of tumour markers, various techniques aimed at increasing detection sensitivity are used. One of the methods of immobilizing bioreceptor molecules is to use nanoparticles of various nature -magnetic (Chen et al 2007, Wei et al 2010 or gold (Tang et al 2006, Tang et al 2008, Uludağ and Tothill 2010, as well as calixarene (Lee et al 2003).…”
Section: Tumour Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine low concentrations of tumour markers, various techniques aimed at increasing detection sensitivity are used. One of the methods of immobilizing bioreceptor molecules is to use nanoparticles of various nature -magnetic (Chen et al 2007, Wei et al 2010 or gold (Tang et al 2006, Tang et al 2008, Uludağ and Tothill 2010, as well as calixarene (Lee et al 2003).…”
Section: Tumour Markersmentioning
confidence: 99%
“…In order to increase the stability of the biolayer a method of immobilizing protein molecules (antigens or antibodies) is proposed using the bifunctional linkers and calixarenes "Prolinkers" (Lee et al 2003). It is shown that the activation of a solid surface by Prolinkers (Fig.…”
Section: Tumour Markersmentioning
confidence: 99%
“…Novel surfaces for Ab adsorption with improved orientation have recently been reported. Surfaces covered with calixarene derivatives have been demonstrated to capture Abs with a proper orientation [10,11]. In addition, Zn II metal complexes have been used for Ab adsorption [12,13].…”
Section: Physical Adsorptionmentioning
confidence: 99%
“…A recent a⁄nity-based method uses calixcrown-5 derivatives. 40 An aldehyde or thiol-activated calixcrown derivative is attached to the substrate surface. Proteins can then bind to the immobilized calixcrown via electrostatic interactions between the ionized amide groups on the protein and the crown moiety.…”
Section: Protein Deposition and Immobilizationmentioning
confidence: 99%